Pastoral power, sovereignty and class: Church, tithe and simony in Quebec. (August 2017) - Curtis, Bruce
Michel Foucault's analysis of pastoral power has generated a large body of work in many different disciplines. Much of it has considered the paradox of the power of "each and all" or has seen pastoral power as an extension of the disciplinary gaze into welfare state policy. The political economy of the pastorate and the mutual dependence of sovereign and pastoral power, by contrast, are both relatively neglected. This article focuses on the exercise of pastoral power in a moral and political economy and examines the "arts of government" through which the Catholic Church attempted to claim that pastors lived from the flock only to live for it. While there is heuristic value in Foucault's diagram of pastoral power, in practice that power cannot be separated from class relations and political sovereignty. Empirical material is drawn from the novel attempt of Britain to govern its Quebec colony through the Catholic Church.